Personality and learning styles towards the practical-based approach - Awang, Halizah; Dollah, Ahmad; Yusof, Yusmarwati; Muhammad Hanafi, Nurfirdawati; Mohd Faiz, Nur Sofurah (IJIET, 2017)
An enduring question for educational research is the result of individual deviations in the efficacy of learning. The individual learning differences that have been much explored relate to differences in personality, learning styles, strategies and conceptions of learning. This article studies the personality and the learning style profile exhibited by students in a practical based approach of vocational courses. The relationship between personality and learning styles among students was assessed as the students got along through the curriculum. The analysis show that students are more oriented towards an active learning mode in a practical-based approach. Given a specific instruction, some people will learn more effectively than others due to their individual personality and learning styles. This study will help a vocational instructor and advisors to understand their students and to design instruction that can benefit students to accomplish a respectable performance in their learning process.